BUKU DAN OBSESI: SEBUAH ANALISIS NEW HISTORICISM PADA 'THE MAN WHO LOVED BOOKS TOO MUCH' - Mohammad Ricky Ramadhan Rasyid; Shafwan Nugraha (Program Studi Sastra Indonesia Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
Obsession with books often reflects broader social and cultural values. This research aims to understand the phenomenon of book obsession through a New Historicism approach, focusing on the cases of John Charles Gilkey and Ken Sanders. The method used is a qualitative case study with textual and contextual analysis of the book